2023
DOI: 10.21203/rs.3.rs-2452311/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lenvatinib with or without Stereotactic Body Radiotherapy for Hepatocellular Carcinoma with Portal Vein Tumor Thrombosis: a retrospective study

Abstract: Background and objectives: Patients with hepatocellular carcinoma (HCC) involving portal vein tumor thrombosis (PVTT) are presently lacking effective treatment options. We aimed to compare the efficacy and safety of lenvatinib with or without SBRT for HCC with PVTT. Materials and Methods: This retrospective analysis included 37 patients treated with lenvatinib in combination with SBRT and 77 patients treated with lenvatinib alone from August 2018 to August 2021. Overall survival (OS), progression-free survival… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Therapies that target the VEGF receptor such as axitinib are generally thought to be safe in combination with SBRT [22], though caution should be taken when treating near bowel as one study suggested increased toxicity for the multikinase inhibitors that target VEGF [23]. Generally, away from the bowel, tyrosine kinase inhibitors are cautiously considered safe with SBRT [24], including cabozantinib [25], sunitinib [5], pazopanib [26], sorafenib [27] and Lenvatinib [28]. Immune targeted agents such as IL-2 [29], pembrolizumab and ipilimumab [30] are also generally thought to be safe in combination with SBRT for renal cell carcinoma [31,32], though there is some suggestion that the combination of immunotherapy with intracranial radiosurgery for brain metastases may increase treatment related inflammatory changes [33].…”
Section: Integration Of Systemic Therapy and Sbrtmentioning
confidence: 99%
“…Therapies that target the VEGF receptor such as axitinib are generally thought to be safe in combination with SBRT [22], though caution should be taken when treating near bowel as one study suggested increased toxicity for the multikinase inhibitors that target VEGF [23]. Generally, away from the bowel, tyrosine kinase inhibitors are cautiously considered safe with SBRT [24], including cabozantinib [25], sunitinib [5], pazopanib [26], sorafenib [27] and Lenvatinib [28]. Immune targeted agents such as IL-2 [29], pembrolizumab and ipilimumab [30] are also generally thought to be safe in combination with SBRT for renal cell carcinoma [31,32], though there is some suggestion that the combination of immunotherapy with intracranial radiosurgery for brain metastases may increase treatment related inflammatory changes [33].…”
Section: Integration Of Systemic Therapy and Sbrtmentioning
confidence: 99%